O181 SERUM C-REACTIVE PROTEIN CAN BE AN EARLY PREDICTOR OF LENGHT OF HOSPITAL STAY AFTER MINIMALLY INVASIVE OESOPHAGECTOMY. (23rd November 2019) - Corsi, Gabriele; Patel, Krashna; Abbassi, Omar; Gudkalli, Zobia; O'Hara, David; Tang, Cheuk-Bong; Jayanthi, Naga Venkatesh; Zanotti, Daniela; Charalabopoulos, Alexandros; Lorenzi, Bruno
Abstract: Aim: Oesophagectomy is associated with a significant number of potential complications affecting the lenght of the post-operative recovery. Serum C-reactive protein (CRP) is an acute phase protein which has been linked to early detection of post-operative complications, including but not limited to anastomotic leak. The aim of this retrospective study was to investigate the value of CRP elevation in the early post-operative days as a predictor of lenght of Hospital stay after minimally invasive oesophagectomy for cancer. Background and Methods: The study group included 88 patients undergoing minimally invasive oesophagectomy for cancer from September 2017 to April 2019. CRP values on post-operative day 1, 3, 5 and 7 were retrieved and correlated to overall lenght of stay. Post-operative morbidity and mortality were also recorded. Results: The approach was fully minimally invasive in 65 patients (74%) and hybrid in the remaining 23 (26%). The median length of stay was 11 days (IQR, 6-105 days) with overall mortality of 3.4% (n=3). Gastro-intestinal complications occurred in 15 patients (17%). The overall surgical or endoscopic re-intervention rate was 13.6% (n=12). The median CRP value was 54.8, 167, 143 and 134 mg/L, respectively on day 1, 3, 5 and 7. There was a positive correlation between CRP and length of stay on day 1, 3 and 7. A cut-off value of 167 mg/L on day 3 appeared to be a significant predictor of increased lenght of stay (12.8 vs 23.3 days, p=0.008). Conclusion: CRP levels above 167mg/L on post-operative day 3 were associated with a prolonged lenght of hospital stay in our group of patients. Elevated CRP in the early post-operative period could represent a useful tool to predict lenght of stay after minimally invasive oesophagectomy.